Theocratic Legal Revolution and the Origins of Modern Secularism in Dante - Miguel Vatter (Síntesis. Revista de Filosofía, 2019)
This article discusses an anti-sovranist variant of political theology. Recent work on the sociology of modern constitutionalism has identified its source in the so-called Papal legal revolution that proclaimed the autonomy of the Church in relation to the Empire. The claim is that this legal revolution contributed to the “secularization” or de-sacralization of political power and established legali-ty as the principle of legitimacy. This paper critically discusses this genealogy of constitutionalism. It proposes an alternative route to modern secularism and constitutionalism that passes through the reception of Averroistic doctrines in the philosophy of Dante.